2020
DOI: 10.1073/pnas.1916238117
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal dynamic monitoring of fatty acid–receptor interaction on single living cells by multiplexed Raman imaging

Abstract: Numerous fatty acid receptors have proven to play critical roles in normal physiology. Interactions among these receptor types and their subsequent membrane trafficking has not been fully elucidated, due in part to the lack of efficient tools to track these cellular events. In this study, we fabricated the surface-enhanced Raman scattering (SERS)-based molecular sensors for detection of two putative fatty acid receptors, G protein-coupled receptor 120 (GPR120) and cluster of differentiation 36 (CD36), in a spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Here, we use surface-enhanced Raman scattering (SERS) microspectroscopy for the analysis of the cell membrane in living cells, and we investigate its potential to study the distribution of lipids and proteins and their interactions. SERS microspectroscopy can be used as a molecular imaging technique, as it provides molecular fingerprints based on Raman vibrational bands of different species of the cellular membrane, including receptor proteins, , signaling molecules at the membrane, and also lipids. , While normal Raman spectroscopy has quite extensively been used in different studies of lipids in cells and cell membranes and in elucidating lipid–lipid and lipid–protein interactions at the microscopic and macroscopic scales, in SERS, signal strength is increased, and selectivity can be introduced due to highly localized probing, since the SERS signal is obtained as result of a very localized interaction . By introducing SERS substrates to cellular models, lipid components were observed based on SERS in the outer cell membrane, in endolysosomal structures, , in parasite-infected cells, and in exosomes …”
Section: Introductionmentioning
confidence: 99%
“…Here, we use surface-enhanced Raman scattering (SERS) microspectroscopy for the analysis of the cell membrane in living cells, and we investigate its potential to study the distribution of lipids and proteins and their interactions. SERS microspectroscopy can be used as a molecular imaging technique, as it provides molecular fingerprints based on Raman vibrational bands of different species of the cellular membrane, including receptor proteins, , signaling molecules at the membrane, and also lipids. , While normal Raman spectroscopy has quite extensively been used in different studies of lipids in cells and cell membranes and in elucidating lipid–lipid and lipid–protein interactions at the microscopic and macroscopic scales, in SERS, signal strength is increased, and selectivity can be introduced due to highly localized probing, since the SERS signal is obtained as result of a very localized interaction . By introducing SERS substrates to cellular models, lipid components were observed based on SERS in the outer cell membrane, in endolysosomal structures, , in parasite-infected cells, and in exosomes …”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, reduced levels were observed upon interaction with D2. Zhang et al using SERS mapping were able to unravel the roles of two fatty acid receptors, G protein‐coupled receptor 120 (GPR120) and a cluster of differentiation 36 (CD36), together as the primary factor in the activation of the fatty acid uptake cycle (Figure 5a; Zhang, Lin, et al, 2020). Other studies include interrogating cellular stress response (Escoriza et al, 2007), monitoring cellular function (Huh et al, 2009), and probing the functional state of the cell nucleus (Xie et al, 2009).…”
Section: Sers Using Intracellular Probesmentioning
confidence: 99%
“…Their method received more widespread attention within the cellular context after Kneipp et al in 2002 demonstrated SERS-based mapping of the distribution of the native chemical constituents phenylalanine and DNA in a single cell (Kneipp et al, 2002). Since then, the interest in the cellular application of SERS has increased substantially with many emerging new developments including SERSbased monitoring of metabolites, imaging intrinsic biomolecules, studying molecular dynamics, and probing cell surface receptor-ligand binding interactions (Ando et al, 2011;Koike et al, 2020;Zhang, Lin, et al, 2020;Zheng, Zong, et al, 2019). Efforts are being carried out to further improve the sensitivity and reproducibility of SERS by designing novel SERS-detectable nanostructures that provide comprehensive insights into biological systems (Kang et al, 2015;Zong et al, 2018).…”
mentioning
confidence: 99%
“…They were able to successfully visualize and monitor the distribution changes and extracellular interaction between fatty acids and receptors by means of SERS imaging. 52 By developing different gold nanostructures using amyloid b (Ab) monomer and fibrils as templates, Zhou et al were able to monitor the Ab aggregation process in neurons and brain tissue in real time with ratiometric SERS imaging. The effects of Cu 2+ , Zn 2+ , and Fe 3+ on Ab aggregation were also studied.…”
Section: Introductionmentioning
confidence: 99%
“…They were able to successfully visualize and monitor the distribution changes and extracellular interaction between fatty acids and receptors by means of SERS imaging. 52 …”
Section: Introductionmentioning
confidence: 99%